Leveraging mobile health technology towards Achieving Universal Health Coverage in Nigeria - Abdulhammed Opeyemi Babatunde; Ahmad Abdullateef Abdulkareem; Foluso Olugbenga Akinwande; Aminat Olaitan Adebayo; Ebelechukwu Tabitha Omenogor; Yusuff Adebayo Adebisi; Esther Bosede Ilesanmi (Elsevier, 2021)
Universal Health Coverage (UHC) is ensuring everyone has access to quality health services needed without suffering any financial hardship. Most African countries including Nigeria are striving to meet this target since the declaration but so far, as of 2020, Nigeria has only made little progress in achieving this goal which was declared to be achieved by 2030. Meanwhile, incorporating Mobile health technology (mHealth) has prospective benefits for achieving UHC by improving access to health care services particularly for those in hard-to-reach communities, enhancing knowledge and access to health information for health workers and communities leading to; increase in productivity of the health workforce, and access to quality healthcare services. Although mHealth has good prospect of promoting the achievement of UHC in Nigeria but there are limitations of poor power supply, poor data collection from evidence-based researches, and restricted access to mobile phones and internet especially in core rural communities in Nigeria. We aim to discuss how mHealth can be leveraged on in promoting achievement of UHC and the challenges associated with incorporating appropriate technology in the Nigerian healthcare system.